Rice farmers' perception and attitude toward organic farming adoption - Ashari; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin; Terano, Rika (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
Back to nature lifestyle emerges as people were more aware against the adverse impacts of agro-chemical inputs in the early 21st century. This phenomenon has led the consumers, particularly for upper-middle income, to consume healthy foods. It implies that the organic farming has a good prospect in forthcoming years. However, the intention of farmer to practice organic farming is still low as indicated by slow rate of adoption. The literature review reveals that perception on innovation characteristics has a significant contribution on adoption behavior. Objective of this study is to examine the farmers’ perception, namely perceived usefulness, perceived risk, environmental concern, as well as attitude affecting their intention to adopt organic farming. This study involves 600 rice farmers as respondents in Sragen Regency, Central Java. The respondents were grouped into two categories namely semi-organic and conventional farmers. The data were collected through a structured questionnaire in May–August 2015. The results show that the perceived usefulness, environmental concern, and attitude positively and significantly affect intention to adopt rice organic farming from both of semi and conventional farmers. Meanwhile, the perceived risk influences negatively on intention to adopt organic rice farming merely for conventional farmers. It is concluded that the perceptions and attitude have significant effect on intention. Therefore, efforts should be undertaken to raise positive farmers’ perception and attitude. Farmers also need supports from several parties to encourage them to involve in organic rice farming.